Method to estimate the user”™s average throughput for an operating base station using Monte Carlo simulation. - Vélez Díaz, Juan; Viñas, Jesús; García, Javier (Rev. Téc. Fac. Ing. Univ. Zulia, 2013)
The following work shows a procedure for determining the behavior of the data throughput for an operating cellular base station as a function of signal to noise plus interference ratio using the Monte Carlo method. First, a flow chart is presented illustrating the main tasks to be carried out. Then, each task is de- scribed including an example applied to the case study. Next, the results obtained by applying the method are presented. The method shows how to combine actual field measurements with simulation to under- stand the possibilities of HSDPA services for a particular base station and its behavior under different situations, saving time to the design engineer and allowing the completion of tests that are difficult to carry out in the field.